Review Article: Regenerative Techniques for Repair of Rotator Cuff Tears. (August 2013) - Ahmad, Zafar; Henson, Fran; Wardale, John; Noorani, Ali; Tytherleigh-Strong, Graham; Rushton, Neil
The failure rate of rotator cuff repair is high. Regenerative techniques using material scaffolds, stem cells, and growth factors help augment repair and regenerate tissue. We reviewed the literature of various regenerative techniques in terms of (1) enhancing the repair process, (2) tissue regeneration, (3) mechanical strength, and (4) clinical outcome.